Development of a broadly active influenza intranasal vaccine adjuvanted with self-assembled particles composed of mastoparan-7 and CpG - Ontiveros-Padilla, Luis; Batty, Cole J.; Hendy, Dylan A.; Pena, Erik S.; Roque, John A.; Stiepel, Rebeca T.; Carlock, Michael A.; Simpson, Sean R.; Ross, Ted M.; Abraham, Soman N.; Staats, Herman F.; Bachelder, Eric M.; et al. (Frontiers in Immunology, 2023)
Currently licensed vaccine adjuvants offer limited mucosal immunity, which is needed to better combat respiratory infections such as influenza. Mast cells (MCs) are emerging as a target for a new class of mucosal vaccine adjuvants. Here, we developed and characterized a nanoparticulate adjuvant composed of an MC activator [mastoparan-7 (M7)] and a TLR ligand (CpG). This novel nanoparticle (NP) adjuvant was co-formulated with a computationally optimized broadly reactive antigen (COBRA) for hemagglutinin (HA), which is broadly reactive against influenza strains. M7 was combined at different ratios with CpG and tested for in vitro immune responses and cytotoxicity. We observed significantly higher cytokine production in dendritic cells and MCs with the lowest cytotoxicity at a charge-neutralizing ratio of nitrogen/phosphate = 1 for M7 and CpG. This combination formed spherical NPs approximately 200 nm in diameter with self-assembling capacity. Mice were vaccinated intranasally with COBRA HA and M7-CpG NPs in a prime–boost–boost schedule. Vaccinated mice had significantly higher antigen-specific antibody responses (IgG and IgA) in serum and mucosa compared with controls. Splenocytes from vaccinated mice had significantly increased cytokine production upon antigen recall and the presence of central and effector memory T cells in draining lymph nodes. Finally, co-immunization with NPs and COBRA HA induced influenza H3N2-specific HA inhibition antibody titers across multiple strains and partially protected mice from a challenge against an H3N2 virus. These results illustrate that the M7-CpG NP adjuvant combination can induce a protective immune response with a broadly reactive influenza antigen via mucosal vaccination.